Dicta Probantia: análise da hermenêutica do estilo de vida do jovem adventista - Meira Junior, Isaac Malheiros (2015)
This research aims to identify and analyze the use of the biblical interpretation method named "proof-text method" among Seventh-day Adventists (1986-2013) in the literature about the lifestyle of young Adventist, and its influence on the hermeneutics of Adventist youth. The first chapter is a historical description of the "proof-text method", its origins and presence in Christianity in general and in particular in Adventism. It also makes a distinction between this method and other hermeneutical resources used in Adventist theology, and a brief review of the method in the light of adventist official hermeneutical principles. The second chapter assesses the presence of the "proof-text method" in guidance materials on the lifestyle of young Adventist, produced and published by the Adventist Church Seventh Day in the 1986-2013 period. Finally, the third chapter analyzes the influence of the use of the "proof-text method" in spirituality and hermeneutical training of young Adventists, using the theory of "Stages of Faith" proposed by James Fowler.